2021
DOI: 10.14434/jotlt.v10i1.31621
|View full text |Cite
|
Sign up to set email alerts
|

Faculty Perceptions of Teaching Online During the COVID-19 University Transition of Courses to an Online Format

Abstract: As a result of the novel coronavirus (COVID-19) pandemic, many universities were required to make quick decisions to accommodate social distancing guidelines. Cherished university events such as commencement and spring convocations were postponed or cancelled. Such decisions were made in an effort to curb the number of people infected with the virus. Institutions were also forced to consider how to continue educating students in the midst of a pandemic. In many instances, faculty were required to transition th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 21 publications
(24 reference statements)
2
15
0
3
Order By: Relevance
“…All of these factors could contribute to a negative perception of using online tools during the pandemic, but, perhaps if given time and proper training, confidence might increase and a willingness to use online tools be seen to grow (Jisc, 2021a;Recker et al, 2007;Wali & Popal, 2020). As Kerr-Sims & Baker (2021) have noted: 'the development of online courses in higher education does not just happen overnight ' (p. 347).…”
Section: The Use Of Online Tools During Online Teachingmentioning
confidence: 99%
“…All of these factors could contribute to a negative perception of using online tools during the pandemic, but, perhaps if given time and proper training, confidence might increase and a willingness to use online tools be seen to grow (Jisc, 2021a;Recker et al, 2007;Wali & Popal, 2020). As Kerr-Sims & Baker (2021) have noted: 'the development of online courses in higher education does not just happen overnight ' (p. 347).…”
Section: The Use Of Online Tools During Online Teachingmentioning
confidence: 99%
“…Depending on the college or university, nursing classes can start in the first, second or third (junior) year; however, core nursing courses and the clinical nursing components are taught mostly in the last two years of the nursing program [62]. For core nursing courses taught in traditional classroom settings, faculty members had to rapidly learn new technologies to enable them to transition effectively and teach their content areas [63]. Faculty members received multiple virtual training workshops on how to teach using the customizable collaborative platform.…”
Section: Development and Accentuation Of Academic Support Servicesmentioning
confidence: 99%
“…The fast-tracked training was executed by faculty members over a 2-week period during which faculty members were expected to be prepared to teach the second half of the semester virtually in Spring 2020. The faculty did not neglect to reach out for technical and technological support, training and mentoring in 2020, proving useful in 2021 when mitigations continued to stay in place in various places around the world [63,65]. Nonetheless, the fast transition was perceived to be overwhelming by students and faculty members [66].…”
Section: Development and Accentuation Of Academic Support Servicesmentioning
confidence: 99%
“…Klasen et al [ 4 ] adds that the dramatic shift in student engagement was due to students assuming multidimensional roles to succeed, given the pandemic’s psychological and educational challenges, such as increased cognitive load and learning responsibility. In their research of 158 faculty members, Kerr-Sims and Baker [ 10 ] found that faculty reported declining student engagement and performance during the pandemic.…”
Section: Introductionmentioning
confidence: 99%